Recovery of the control plane after failures in ASON - Jajszczyk, A.
A reliable control plane plays a crucial role in creating high-level services in the next-generation transport network based on the generalized multiprotocol label switching (GMPLS) or automatically switched optical networks (ASON) model. Approaches to control-plane survivability, based on protection, and restoration mechanisms, are examined. Procedures for the control plane state recovery are discussed, including link and node failure recovery
Keywords: ASON; GMPLS networks; Automatically switched optical networks; Control plane state recovery; Control-plane survivability; Generalized multiprotocol label switching; Next-generation transport network; Node failure recovery; Reliable control plane; Restoration mechanisms